Cerebral protection by remote ischemic post-conditioning in patients with ischemic stroke: A systematic review and meta-analysis of randomized controlled trials - Lu, Meng; Wang, Yujiao; Yin, Xin; Li, Yuanyuan; Li, Hongyan (Frontiers in Neurology, 2022)
Abstract Background: There is evidence that remote limb ischemic postconditioning (RIPostC)can reduce ischemia-reperfusion injury (IRI) and improve the prognosis of patients with ischemic stroke. However, so far, only few relevant clinical studies have been conducted. Therefore, we carried out a meta-analysis of eligible randomized controlled trials to compare the RIPostC group with a control group (no intervention or sham surgery) in patients with ischemic stroke. Methods: Four English-language publication databases, PubMed, Cochrane, Embase, and Web of Science, were systematically searched up to March 2022. The data were analyzed using Review Manager fixed-effects and random-effects models. Results: A total of 12 studies were included, and 11 of those were analyzed quantitatively. Compared to controls, The RIPostC group showed significantly reduced NIHHS scores in patients with ischemic stroke, (MD: -1.09, 95% confidence interval [CI]: -1.60, -0.57, P＜0.0001) and improved patients' Montreal Cognitive Assessment(MoCA) scores, (MD: 1.89, 95% CI : 0.78, 3.00, P=0.0009), Our results showed that RIPostC is safe, (RR=0.81, 95%CI: 0.61，1.08, P=0.15). Conclusion: Our meta-analysis showed that RIPostC is safe and effective and has a positive cerebral protective effect in patients with ischemic stroke, which is safe and effective, and future large-sample, multicenter trials are needed to validate the cerebral protective effect of RIPostC.